2015
DOI: 10.1007/s00122-015-2606-x
|View full text |Cite
|
Sign up to set email alerts
|

Toward a better understanding of the genomic region harboring Fusarium head blight resistance QTL Qfhs.ndsu-3AS in durum wheat

Abstract: New molecular markers were developed and mapped to the FHB resistance QTL region in high resolution. Micro-collinearity of the QTL region with rice and Brachypodium was revealed for a better understanding of the genomic region. The wild emmer wheat (Triticum dicoccoides)-derived Fusarium head blight (FHB) resistance quantitative trait locus (QTL) Qfhs.ndsu-3AS previously mapped to the short arm of chromosome 3A (3AS) in a population of recombinant inbred chromosome lines (RICLs). This study aimed to attain a b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 42 publications
0
21
0
Order By: Relevance
“…More distantly related wild and cultivated relatives, e.g. T. dicoccoides, T. dicoccum and T. carthlicum, were screened to broaden the base of resistant sources for durum wheat (2003a, 2003aOliver et al 2007Oliver et al , 2008, but resistances found therein do not come close to the strong QTL detected in hexaploid wheat (Prat et al 2014;Zhang et al 2014;Zhu et al 2016b). …”
Section: Resistance Sources and Qtlmentioning
confidence: 99%
See 1 more Smart Citation
“…More distantly related wild and cultivated relatives, e.g. T. dicoccoides, T. dicoccum and T. carthlicum, were screened to broaden the base of resistant sources for durum wheat (2003a, 2003aOliver et al 2007Oliver et al , 2008, but resistances found therein do not come close to the strong QTL detected in hexaploid wheat (Prat et al 2014;Zhang et al 2014;Zhu et al 2016b). …”
Section: Resistance Sources and Qtlmentioning
confidence: 99%
“…The authors demonstrate that the gene does not confer resistance against DON suggesting that toxin resistance is under different genetic control in the same genetic block (Rawat et al 2016). For several other resistance QTL fine-mapping and cloning approaches are underway, which will result in the development of diagnostic markers for resistance QTL to be easily adopted by breeders (Cuthbert et al 2007;Xue et al 2010Xue et al , 2011Zhu et al 2016b). …”
Section: Identification Of the Genes Behind The Qtlmentioning
confidence: 99%
“…Hermon#22, and Mt. Gerizim#36 have been identified on chromosomes 3A (Otto et al 2002; Gladysz et al 2007; Chen et al 2007; Buerstmayr et al 2013; Zhu et al 2016b), 4A (Gladysz et al 2007), 6B (Buerstmayr et al 2013) and 7A (Kumar et al 2007). Triticum dicoccum accessions PI 41025, Td-161 and BGRC3487 provided resistance QTL on 3A, 3B, 4B, 5A, 6A, 6B, 7A and 7B (Buerstmayr et al 2012; Ruan et al 2012; Zhang et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…New markers closer to Qfhs. ndsu-3AS have recently become available (Zhu et al 2015). Within MM and Mm progeny, all except for three plants (one MM and two Mm plants from B. Esmeralda × Langdon(Dic-3A)-10 cross) exhibited lower disease scores than the resistant parent (data not shown).…”
Section: Discussionmentioning
confidence: 96%
“…Mapping analysis positioned Qfhs.ndsu-3AS within a chromosomal interval of 11.5 cM that is flanked by markers Xfcp401 and Xfcp397.2, with the microsatellite locus Xgwm2 tightly linked to Qfhs.ndsu-3A (Chen et al 2007). A recent study saturated the Qfhs.ndsu-3AS region using 22 newly EST-derived markers (Zhu et al 2015).…”
Section: Cereal Research Communications 45 2017mentioning
confidence: 99%